P09.01 Cost-effectiveness of testing for trichomonas vaginalis in genitourinary medicine clinics and primary care in england using aptima tv naat. (13th September 2015) - Turner, K; Nicholls, J; Muir, P; North, P; Ferguson, R; May, M; Macleod, J; Horner, P
Abstract : Background: Laboratory tests for Trichomonas vaginalis (TV) using culture and microscopy in current practice have low sensitivity. However new, highly sensitive PCR-based nucleic acid amplification tests (TV NAATs) have been approved e.g. Aptima TV NAAT. It is not known how to optimally deploy these new tests. Objectives: To assess the cost-effectiveness of new TV NAAT tests for the diagnosis of TV infection in women attending genitourinary medicine (GUM) and primary care clinics in England. To inform decision-making about who should be offered TV testing. Methods: We analysed data from TV tests in residual chlamydia/gonorrhoea samples from 9, 000 women. We conducted notes review in GUM clinics to understand current management. We calculated the cost of testing for TV and the cost per additional case detected. Results: The cost of TV test as a new standalone test is £15.19, or £7.62 as an add-on to chlamydia/gonorrhoea NAAT tests. Microscopy/wet prep costs £7.93. Current testing detected only 9/50 GUM and 15/126 primary care cases identified using TV NAAT tests. The crude cost of adding TV to all chlamydia/gonorrhoea NAAT tests and removing microscopy, is £291 per additional case (£139 per symptomatic and £496 per asymptomatic). The cost-effectiveness is sensitive to the underlying positivity (decreases within increasing positivity) and the differences between the amount and sensitivity of current testing practice. Discussion/conclusion: TV NAAT tests detected many more infections than current testing practice. If TV NAAT is added to current chlamydia/gonorrhoea testing in English GUM clinics, this would translate to an increase from 6, 000 TV cases to 23, 400 cases annually. The implications are that testing symptomatic women in GUM and possibly primary care for TV would be beneficial as positivity is similar to chlamydia in these groups. For asymptomatic women a more targeted approach may be more appropriate according to local demographics. Disclosure of interest statement: Hologic provided the tests for the Aptima TV NAAT research study and have sponsored the authors to present this data at ISSTDR.